Pelatihan Peningkatan Kompetensi Guru dalam Penulisan Karya Ilmiah dalam bentuk Jurnal sebagai Pengembangan Profesi Berkelanjutan Guru SMA Kecamatan Pasir Penyu Kabupaten Indragiri Hulu - Isjoni, Isjoni; Azhar, Fadly; Isjoni, M. Yogi Riyantama; Nurdiansyah, Nurdiansyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The purpose of this service is to provide understanding and experience about writing scientific journals in the form of articles to high school teachers of Pasir Penyu District, Indragiri Hulu Regency. It is hoped that with this dedication, all teachers of SMA Pasir Penyu District, Indragiri Hulu Regency can carry out journal writing as teachers' scientific work later. The targets of this service are teachers who are constrained by promotion due to the absence of research as their scientific work.The enthusiasm of teachers in participating in these service activities was quite high, question after question submitted to the resource persons was quite active towards the targets of the Journal itself. At the beginning and until the end of the activity for 4 days (32 hours) most of them understand and the motivation to produce the product is quite high. When the exercise of legion no one does not understand, and that sincerity is seen from time to time in both group and classical discussions. At the end of the service activity, each teacher is required to prepare a product in the form of a proposal, consisting of Chapter I Introduction, Chapter II Literature Review and Chapter III Research Methods. and bibliography. Of the 40 teachers, only 10 have submitted articles to be published in the Journal.